The relationship between happiness and quality of life: A model for Spanish society. - Víctor-Raúl López-Ruiz (Public Library of Science (PLoS), 2021)
A key goal for society as a whole is the pursuit of well-being, which leads to the happiness of its individual members; as such, it is of critical socioeconomic relevance. In this regard, it is important to study which factors primarily affect the happiness of the population. In principle, these factors are associated with income level and residential and job stability, or more specifically, citizens' quality of life. This research, which is based on a multidimensional concept of quality of life, uses a regression model to explain the dependence of Spaniards' happiness on the well-being or quality of life provided by their work, their family situation, their income level and aspects of their place of residence, among other factors. The data were collected through an anonymous survey administered to a representative sample of Spanish citizens. The methodology used approaches the intangible concept of happiness as resulting from different individual and social causes selected from dimensions addressed in the literature, and calculates their effects or importance through regression coefficients. One of the findings is that people with the highest level of well-being or quality of life in the most important dimensions mostly claim to be happy. With respect to gender, it has a significant influence on the dimensions included in the model of citizen happiness and on personal issues. It is also shown that the outbreak of the Covid-19 pandemic negatively influenced the quality of life of Spanish citizens and therefore their happiness.